Association between maternal second-trimester stress and adverse pregnancy outcomes according to pre-pregnancy body mass index and gestational weight gain - Zhang, Lixia; Zhu, Shuqi; Wu, Yihui; Chen, Danqing; Liang, Zhaoxia (Frontiers in Psychiatry, 2023)
Objective: To investigate the impact of maternal second-trimester stress on pregnancy outcomes according to pre-pregnancy body mass index (BMI) and gestational weight gain (GWG). Methods: We did a prospective study in Women’s Hospital, School of Medicine, Zhejiang University and included 960 pregnant women in our final analysis. Obstetric characteristics and the incidence of adverse pregnancy outcomes were examined in stressed and non-stressed women. The associations between maternal prenatal stress with adverse pregnancy outcomes were analyzed by logistic regression. Results: The incidence of premature rupture of membranes (PROM) was significantly higher in stressed pregnant women than non-stressed pregnant women (p=0.035), whereas no significant difference in the incidence rates of gestational diabetes mellitus (GDM), pregnancy-induced hypertension (PIH), primary cesarean delivery, preterm birth, macrosomia, low birth weight, fetal stress, admission into neonatal intensive care unit (NICU) or neonatal jaundice was found between two groups. Maternal second-trimester stress was an independent risk factor for the development of PROM (aOR=1.468, 95% CI 1.037-2.079). Moreover, maternal second-trimester stress was significantly associated with PROM in pregnant women with normal pre-pregnancy BMI (aOR=1.587, 95% CI 1.068-2.357) while no association was observed in either underweight or overweight and obese pregnant women. Meanwhile, no difference was found in the odds of PROM with maternal second-trimester stress in all GWG subgroups. Conclusion: Maternal second-trimester stress is associated with a higher risk of PROM and it’s significant in pregnant women with normal pre-pregnancy BMI. Therefore, interventions to reduce stress during second-trimester of pregnancy might be essential for lowering the prevalence of PROM in pregnant women with normal pre-pregnancy BMI.